2011
DOI: 10.4014/jmb.1101.12040
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Mesophilic Arthrospira maxima Strain Capable of Producing Docosahexaenoic Acid

Abstract: A strain of the cyanobacterium Arthrospira was isolated from Lake Chahannaoer in northern China and was characterized according to microscopic morphology, photosynthetic oxygen-evolving activity, growth rate, and nutritional profile. Compared with thermophilic Arthrospira species occurring naturally in tropical and subtropical lakes, this isolate is mesophilic and grows optimally at 20 o C. The total protein, fatty acid, phycocyanin, carotenoid, and chlorophyll a contents were 67.6, 6.1, 4.32, 0.29, and 0.76 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…MUFA are less abundant than SFA and PUFA are rather unimportant (El-Kassas et al, 2015). Other studies (Hu et al, 2011) have found hexadecanoic and octadeca-9,12-dienoic acids in Arthrospira maxima in percentages very similar to those determined in the current study on A. platensis. Substantial levels of octadeca-9,12-dienoic acid in Arthrospira have also been reported by Palaniswamy & Veluchamy (2017).…”
Section: Fatty Acid Profilesupporting
confidence: 87%
See 2 more Smart Citations
“…MUFA are less abundant than SFA and PUFA are rather unimportant (El-Kassas et al, 2015). Other studies (Hu et al, 2011) have found hexadecanoic and octadeca-9,12-dienoic acids in Arthrospira maxima in percentages very similar to those determined in the current study on A. platensis. Substantial levels of octadeca-9,12-dienoic acid in Arthrospira have also been reported by Palaniswamy & Veluchamy (2017).…”
Section: Fatty Acid Profilesupporting
confidence: 87%
“…Substantial levels of octadeca-9,12-dienoic acid in Arthrospira have also been reported by Palaniswamy & Veluchamy (2017). However, Hu et al (2011) also found non-negligible amounts of DHA and high levels of c-linolenic acids. Since DHA is the longest and most unsaturated FA chain commonly found in biological membranes, it decisively favours membrane fluidity and plays a positive role in low-temperature stress tolerance, which may explain DHA presence in A. maxima biomass, given this species' mesophilic nature (Hu et al, 2011).…”
Section: Fatty Acid Profilementioning
confidence: 93%
See 1 more Smart Citation
“…Protein content in cyanobacteria selected for this review[41,46,64,[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92] 1 .…”
mentioning
confidence: 99%
“…1) la intensidad y tipo de luz; 2) la concentración de NaCl (Chainapong et al, 2012); 3) la fuente de nitrógeno (Ajayan et al, 2012), pero no es tan determinante como en el caso de la FC; 4) la temperatura (Hu et al, 2011).…”
Section: Producción De Carotenoides En Arthrospira: β-Carotenounclassified